Comparison of 180° and 360° Arc Data Acquisition to Measure Scintigraphic Parameters from Gated Single Photon Emission Computed Tomography Myocardial Perfusion Imaging: Is There Any Difference? - Javadi, Hamid (Mol Imaging Radionucl Ther, 2016)
OBJECTIVE: The aim of the current study was to compare 180° and 360° data collection modes to measure end diastolic volume (EDV), end systolic volume (ESV) and ejection fraction (EF) values of the cardiac system by gated myocardial perfusion tomography. METHODS: Thirty-three patients underwent gated myocardial perfusion tomography. Single photon emission computed tomography data of patients’ heart were acquired by 180°, 45° left posterior oblique to 45° right anterior oblique, and 360° to obtain EDV, ESV, EF and cardiac volume changes (V1, V2, V3, V4, V5, V6, V7 and V8) throughout each cardiac cycle. RESULTS: Results of the current study indicated that there were no significant differences between 180° and 360° angular sampling in terms of measuring EDV, ESV and EF in myocardial perfusion imaging. Cardiac volume change patterns during a cardiac cycle were also similar in 360° and 180° scans. We also observed that there was no difference in EDV, ESV and EF values between the group with stress induced by exercise and the group with stress imposed by dipyridamole. CONCLUSION: As there is no difference between 180°and 360° cardiac scanning in terms of EDV, ESV and EF, half-orbit scan is recommended to study these cardiac system parameters because it offers more comfort to patients and a shorter scanning time.